2022
DOI: 10.3390/jcm11154551
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors Affecting the Recurrence of Primary Retinal Detachment in a Tertiary Hospital in Spain

Abstract: (1) Objective: To determine the incidence, visual outcomes and risk factors associated with the recurrence of primary retinal detachment (RD) in a tertiary hospital. (2) Methods: A retrospective observational study was conducted, and data were collected on all eyes diagnosed with primary RD between January 2017 and December 2020. A detailed database was generated with data on anatomic and visual outcomes, and surgical technique information, for all the cases. (3) Results: 570 eyes with primary RD were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…According to the previous literatures, the possible risk factors for Re RD after anatomical successful RRD surgery are male gender, poor baseline BCVA, hypotony, pseudophakic status, long-standing RRD, inferior breaks, presence of PVR (especially Grade ≥ C), and type of tamponade. 15 , 17 , 18 In logistic regression analysis, we showed that lower BCVA before the initial surgery (probably an indicator of complicated RD), had a statistically significant relationship with the occurrence of unplanned reoperation, and other variables including primary diagnosis, lens status, and type of primary surgery and tamponade did not have significant relations with the occurrence of unplanned return to the operation room. In addition, for demographic factors including age and sex variables, there were no significant differences in cases with unplanned reoperations compared to those without, similar to the Stewart et al .’s 7 study.…”
Section: Discussionmentioning
confidence: 85%
“…According to the previous literatures, the possible risk factors for Re RD after anatomical successful RRD surgery are male gender, poor baseline BCVA, hypotony, pseudophakic status, long-standing RRD, inferior breaks, presence of PVR (especially Grade ≥ C), and type of tamponade. 15 , 17 , 18 In logistic regression analysis, we showed that lower BCVA before the initial surgery (probably an indicator of complicated RD), had a statistically significant relationship with the occurrence of unplanned reoperation, and other variables including primary diagnosis, lens status, and type of primary surgery and tamponade did not have significant relations with the occurrence of unplanned return to the operation room. In addition, for demographic factors including age and sex variables, there were no significant differences in cases with unplanned reoperations compared to those without, similar to the Stewart et al .’s 7 study.…”
Section: Discussionmentioning
confidence: 85%